1997
DOI: 10.3853/j.0067-1975.49.1997.249
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and ecological disparity in naraoiids (Arthropoda) from the Early Cambrian Chengjiang Fauna, China

Abstract: ABSTRACT. Misszhouia longicaudata (Zhang & Hou) from the Chengjiang lagerstatte is separated from Naraoia Walcott by its antennular orientation, its smaller cephalic caeca and gut, lanceolate distal exopod lobe, and partial fusion of the exopod and first endopodal podomere. Naraoia spinosa Zhang & Hou (also from Chengjiang) shares derived characters with the type species, N. compacta. Deposit feeding is suggested for Naraoia spinosa by both morphology and preservational circumstances. New material shows previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 0 publications
3
92
0
3
Order By: Relevance
“…The appendage morphology of Naraoia is well-known (Whittington 1977; see also refinements in Ramsköld and Edgecombe 1996), and its massive, spiny basal endites ('gnathobases') leave little room for doubt that the habits of some species of Naraoia were predatory: 'Naraoia appears to have been particularly welladapted to capture and to feed on the varied, small, worm-like creatures that abounded in the Burgess Shale' (Whittington 1977, p. 438). Chen et al (1997) have suggested that one Naraoia species from the Lower Cambrian of China may have rather lived by ingesting sediment, indicating a wider diparity of feeding habits within naraoiids as a whole. But the evidence derived from the majority of closest-related sister taxa points to predatory habits for olenelloids also.…”
Section: P R I M I T I V E P R E D a T O R Y F E E D I N G H A B I T mentioning
confidence: 99%
See 2 more Smart Citations
“…The appendage morphology of Naraoia is well-known (Whittington 1977; see also refinements in Ramsköld and Edgecombe 1996), and its massive, spiny basal endites ('gnathobases') leave little room for doubt that the habits of some species of Naraoia were predatory: 'Naraoia appears to have been particularly welladapted to capture and to feed on the varied, small, worm-like creatures that abounded in the Burgess Shale' (Whittington 1977, p. 438). Chen et al (1997) have suggested that one Naraoia species from the Lower Cambrian of China may have rather lived by ingesting sediment, indicating a wider diparity of feeding habits within naraoiids as a whole. But the evidence derived from the majority of closest-related sister taxa points to predatory habits for olenelloids also.…”
Section: P R I M I T I V E P R E D a T O R Y F E E D I N G H A B I T mentioning
confidence: 99%
“…Papyriaspis). Such caecal patterns have been attributed to digestive glands (Ö pik 1961;Cisne 1975;Chen et al 1997), and, if so, might be supposed to have yielded secretions which aided digestion of the particulate organic material sorted by the trunk limbs. Such a digestive system might account for the comparatively small volume of the stomach in these trilobites; much of the work would have been done by digestive enzymes.…”
Section: Uncalcified Anatomymentioning
confidence: 99%
See 1 more Smart Citation
“…Whittington 1975Whittington , 1980. A similar morphology of the exopod has been found in different species of Naraoia Walcott, 1912 (Whittington 1977, Chen et al 1997, Hou & Bergström 1997, a reason why these were often considered to be a kind of soft trilobites (e.g. Whittington 1977).…”
mentioning
confidence: 94%
“…The medusiform eldoniids (and rotadiscids) are a characteristic component of Burgess Shale-type faunas. In addition to their type occurrence in the Burgess Shale (Walcott, 1911b;Durham, 1974;Friend, 1995), this group is recorded from other Lower (e.g., Chen et al, 1995;Chen and Zhou, 1997) and Middle Cambrian localities in China (Zhao and Zhu, 1994;Dzik et al, 1997), Siberia (Friend et al, 2002), Poland (Masiak and Zylińska, 1994), and Utah (Conway Morris and Robison, 1988) Taxonomic affinities of the eldoniids have remained controversial (e.g., Zhu et al, 2002). One suggestion has been to link them to the lophophorates (e.g., Dzik et al, 1997).…”
Section: Superphylum Ambulacraria Metschnikoff 1881mentioning
confidence: 99%